Comparison of Insertion Characteristics of Prewarmed Igel and I-gel at Room Temperature in Adult Patients Undergoing Elective Surgeries- A Randomized Control Trial - Priyanka Pathak; Mushtaq Wani; Heena Saini (JK Science)
Background: I-gel is usually inserted at room temperature, but in certain studies it was found that I-gel may mould to the laryngeal structures faster if pre-warmed. Aim: The present study was conducted to investigate this hypothesis by comparing the airway sealing pressure and leak volume amount between prewarmed Igel devices and those kept at room temperature in paralysed adult patients on Volume Controlled Ventilation mode of ventilator posted for elective surgeries. Material and Methods: 70 patients were randomly allocated into 2 groups using computer generated randomisation. In Group C, airway was secured with Igel at room temperature. In Group W, patients airway was secured with I-gel which was prewarmed at 42˚Celsius. Results: The mean insertion time of prewarmed I-gel was 11.94 ± 1.59 seconds whereas that of I-gel at room temperature was 14.20 ± 1.80 seconds which was statistically significant. Mean leak volume after one minute and 30 minutes of insertion in W group was lesser than C group and the difference was statistically significant (p=0.048). Conclusion: Prewarmed I-gel does not provide a higher sealing pressure or better insertion success rate even in the presence of muscle relaxants. However, prewarmed I-gel had smaller insertion time and leak volume than control group.